Granulocyte-colony stimulating factor response is superior to neutropenia duration in predicting the risk of infection after high-dose chemotherapy for myeloma and lymphoma. Issue 2 (February 2015) - Straka, Christian; Salwender, Hans; Schnabel, Brigitte; Sandherr, Michael; Wandt, Hannes; Hübel, Kai; Scheid, Christof; Metzner, Bernd; Hentrich, Marcus; Franke, Daniel; Weidenegger, Gloria; Freund, Mathias; et al.
Abstract The patient granulocyte-colony stimulating factor (G-CSF) response is represented by the leukocyte peak in the blood induced by a single dose of G-CSF after chemotherapy, and is correlated with subsequent neutropenic infection risk. General patterns for a meaningful risk group stratification, have not yet been determined. Two independent data sets including a total of 306 cases with myeloma or lymphoma and autologous blood stem cell transplant were available. An infection susceptibility curve plotted according to ranked G-CSF responses from a multicenter study reproduced and validated a curve from the previous single center. Two trend changes were seen within these curves at around 11 000 and 22 000 leukocytes/μL, which separated three groups with a high, medium and low risk of infection. While G-CSF response is related to the consecutive duration of neutropenia, it retains additional independent predictive information for infection risk (p < 0.0001) and, more important, is a tool available before the onset of the critical period.